New data on the genus Megadiestramima Storozhenko & Gorochov, 1992 (Orthoptera: Rhaphidophoridae: Aemodogryllinae), with descriptions of a new subgenus and a new species from Thailand - Dawwrueng, Pattarawich; Gorochov, Andrei V.; Pawangkhanant, Parinya; Suwannapoom, Chatmongkon (Zootaxa, 2025)
The new subgenus and species Megadiestramima (Troglodiestramima) storozhenkoi subgen. & sp. nov. are described from western Thailand. This new subgenus is easily distinguished by the male seventh abdominal tergite with a shortly broad medial process, the posterior edge of this process with numerous small denticles, and the male paraprocts elongate and triangular as well as without any specialized apex. Its female is similar to the subgenus Leodiestramima in the genital plate with an angular posteromedian process, but the ovipositor apex differs from that of all other subgenera by having small denticles on the ventral edge. We also provide an additional record of Megadiestramima (Leodiestramima) lecta Gorochov, 1998 from Ratchaburi Province and some data on its biology.